Effect of defect width upon burst capacity of composite repaired pipe - Leong, Kah En (2019)
In recent years, application of FRP composite in repairing steel pipeline is the most preferable pipeline rehabilitation system used in the pipeline industry. However, some issues about this repair method are not fully understood by the industry. Effect of defect geometry toward the efficiency of composite repair pipe is one of the issues that concerned by the industry. Design codes and standards of pipeline repair method have been developed mainly focus on defect depth and neglect other defect geometries such as defect length and defect width in repairing damaged pipeline. Past researches show that these codes and standard are considered conservative and there are rooms for optimization. Previous studies states that defect geometry especially defect width should not be ignored in evaluating and designing pipe repair system. This is also proven in some of the assessment codes that used defect geometry as one of the parameter to effectively assess the condition of pipe. Therefore, the burst pressure of the defective pipeline subjected to various defect widths is determined through this study in order to evaluate the effect of defect width upon the burst capacity of composite repaired pipeline. Finite element analysis was used to determine the burst capacity of the composite repaired pipe with rectangular shape of defect. There are three different widths (D, ½D and 2D, where D is the pipe diameter) were selected for analysis with no changes on defect length and depth. The base model of composite repaired pipe was created, validated and modified with the various defect widths that mentioned before. The result shows that burst pressure for three different models vary with a percentage of 12.51% between the maximum burst pressure and minimum burst pressure. The stress contour plot diagrams that extracted from the finite element analysis also shows that the area of highest stress (557.7MPa) concentration around defect region is getting bigger when the defect width is getting wider with the defect area getting larger. With this, the composite repaired pipe tends to fail at lower pressure when the defect is getting wider. Based on the results, the defect width is proven to affect the burst capacity of composite repaired pipe.